Penghematan Gas H2 Pada Sistem PEMFC (Proton Exchange Membrane Fuel Cell) Sesuai Perubahan Daya Beban - Habibullah - - (Jurnal Ilmiah Poli Rekayasa, 2015)
This project aims to testing the equation which obtained from the graph characteristics relationships of the optimum input voltage driver valve to change the power load on the valve opening proportional to the input PEMFC system so that the valve opening will work automatically according to changes in load power. Equations are taken there are two linear equations and polynomials. Enter the equation is used as the power load and input voltage output driver valves. Test results show similarities with both voltage and output current characteristics are almost the same system with the characteristics of the optimum and maximum valve opening. H2 gas usage on testing with both equations show similar values with optimum valve opening, making it more efficient than the maximum valve opening